'ACCEPTABLE TRUTHS' DURING THE FRENCH RELIGIOUS WARS. (December 2020) - Roberts, Penny
Abstract: This paper seeks to provide some historical perspective on contemporary preoccupations with competing versions of the truth. Truth has always been contested and subject to scrutiny, particularly during troubled times. It can take many forms – judicial truth, religious truth, personal truth – and is bound up with the context of time and place. This paper sets out the multidisciplinary approaches to truth and examines its role in a specific context, that of early modern Europe and, in particular, the French religious wars of the sixteenth century. Truth was a subject of intense debate among both Renaissance and Reformation scholars, it was upheld as an absolute by judges, theologians and rulers. Yet, it also needed to be concealed by those who maintained a different truth to that of the authorities. In the case of France, in order to advance their cause, the Huguenots used subterfuge of various kinds, including the illicit carrying of messages. In this instance, truth was dependent on the integrity of its carrier, whether the messenger could be trusted and, therefore, their truth accepted. Both sides also sought to defend the truth by countering what they presented as the deceit of their opponents. Then, as now, acceptance of what is true depends on which side we are on and who we are prepared to believe.